An Analysis of Students' Errors in Solving Indefinite Integral Problems Viewed From Gender Differences - Hesty Marwani Siregar; Titi Solfitri (Journal of Research on Mathematics Instruction (JRMI), 2019)
Based on previous research, one of the gender differences between men and women in mathematics is problem solving skills. Gender differences in mathematical problem solving can be an indication of the different errors experienced by male and female students. The question of this research is what kinds of error are made by students in solving indefinite integrals viewed from gender differences? While the purpose of this research is to describe the type of errors made by students in solving indefinite integrals viewed from gender differences. This research is a qualitative research using a descriptive research methodology approach. The subjects were 3 male students male and 3 female students taken by purposive sampling. Data were collected from indefinite integral test, which are used to determine the type of the students’ fault in solving problem based on indicators Newman. Indefinite integrals in this research regarding indefinite integral by substitution and integration of fractional function by partial fraction. From the result of the study, it was found that for integral substitution problem, all of the male students could solve the problems well, while female students made transformation and process skill errors. In a matter of integration of rational function by partial fractions, 1 male students encountered process skills error, while two other male students encountered comprehension error. For female students, the error that occurs is transformation error.